Family Communication: Strategies for Building Effective Partnerships and Working Relationships - Shamash, Emily R.; Martin, Alyson M. (Journal of the American Academy of Special Education Professionals, 2014)
This article offers a variety of strategies for pre-service and beginning teachers to utilize in order to create positive and effective relationships with families that are built on clear communication and trust. It is crucial for new and veteran teachers to understand the importance of successful communication with parents and families of students with special needs. Teachers and educational professionals should implement ongoing strategies throughout the school year to ensure that parents and families are educated about the approaches and services their child receives in school. Familial knowledge and understanding of the types of services and the schedule of when those services are delivered can lead to increased family involvement in their child’s special education program. This involvement can ultimately increase the learning process and progress towards meeting goals and objectives for students with disabilities (Dunst, 2002; Kashinath, Woods, & Goldstein, 2006, Wellner, 2012). This article will define the following strategies: creating "master schedules," writing a "student at a glance," setting up "team meeting schedules" for the school year, creating "team meeting and IEP meeting agendas," as well as explain the most effective use of "communication sheets." These types of user-friendly approaches to establishing ongoing and consistent contact with families is necessary for family satisfaction and student success, especially for families of students with disabilities at all age levels (Bezdek, Summers, & Turnbull, 2010; Diliberto & Brewer, 2012).